Use of Synonymous in The Qur'an (Semantic Analysis Study) - Al Sayyid, Abdul Rahman; Habibi, Muhammad Yusuf; Arief, Ahmad Fahmy; Husin, Saifudin Ahmad (UIN ANTASARI, 2023)
In the use of language, sometimes we find a difference between one speech and another speech with expressions that have one meaning. This phenomenon is also called by linguists with synonyms. Synonyms are two words that have one or more meanings, such as